2020
DOI: 10.14740/jocmr4228
|View full text |Cite
|
Sign up to set email alerts
|

First Reported Use of Highly Adsorptive Hemofilter in Critically Ill COVID-19 Patients in the USA

Abstract: Critically ill patients with coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) develop respiratory failure and septic shock. Extracorporeal blood purification is proposed as an adjuvant therapy for sepsis and aims at controlling the dysregulated autoimmune system. We describe our experience in treating COVID-19 patients with the oXiris ® hemofilter which adsorbs both cytokines and endotoxins, provides renal replacement therapy and has anti-thrombogenic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 8 publications
(10 reference statements)
0
16
0
Order By: Relevance
“…In the treatment of H7N9-induced severe pneumonia, which is also characterized by ARDS, plasma exchange (PE) combined with continuous veno-venous hemofiltration treatment can significantly reduce serum levels of cytokines and improve outcomes ( 60 ). Several studies have shown the attractive effects of blood purification treatment in relieving cytokine storms and improving the outcomes for patients critically ill with COVID-19 ( 61 63 ). Importantly, better efficacy can be achieved with earlier application of blood purification therapies ( 64 66 ).…”
Section: Immunotherapy Strategies For Patients With Critically Ill Comentioning
confidence: 99%
“…In the treatment of H7N9-induced severe pneumonia, which is also characterized by ARDS, plasma exchange (PE) combined with continuous veno-venous hemofiltration treatment can significantly reduce serum levels of cytokines and improve outcomes ( 60 ). Several studies have shown the attractive effects of blood purification treatment in relieving cytokine storms and improving the outcomes for patients critically ill with COVID-19 ( 61 63 ). Importantly, better efficacy can be achieved with earlier application of blood purification therapies ( 64 66 ).…”
Section: Immunotherapy Strategies For Patients With Critically Ill Comentioning
confidence: 99%
“…oXiris is a highly adsorptive membrane with unique four-in-one properties which include cytokine and endotoxin removal in vitro and in septic shock patients, renal replacement therapy, and anti-thrombogenic features. [ 7 ] It is pre-grafted with Polyethyleneimine (PEI) and an average of 4,500 UI/m 2 heparin during manufacturing, The positively charged free amino groups, in particular linear PEI grafting allows it to adsorb large negatively charged molecules, such as endotoxins and cytokines. This unique design makes the combination of renal support, cytokine removal, endotoxin removal, and local anticoagulant treatment possible in a single device, which is simple to use.…”
Section: Discussionmentioning
confidence: 99%
“…The removal of cytokines via extracorporeal therapies has been an active area of study. 42 , 44 , 45 Extracorporeal treatments should theoretically not interfere with experimental antibody-based therapies used in COVID-19 (e.g., tocilizumab, convalescent plasma, intravenous immunoglobulins), as hemodialysis filters and hemadsorption cartridges do not remove antibodies. The size of these antibodies exceed the size of molecules that can be removed with extracorporeal treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Studies indicate that certain filters can remove inflammatory markers in critically ill COVID-19 patients. 42 , 44 , 45 However, further research is necessary to explain the outcomes related to these therapies.…”
Section: Introductionmentioning
confidence: 99%